Relationship Between Anxiety Levels and Sleep Quality of Health Students - Marisna Eka Yulianita; Andi Risna; Andi Rizky Amaliah; Andi Wahyuni; Irwan Irwan (Althar Cendikia Education, 2025)
Anxiety is a situation in which a person faces a situation in the form of unpleasant emotions. It is known that 40% of Indonesian students experience anxiety and 41.2% of students experience anxiety when doing their final project. In addition, 64.2% of college students experience poor sleep quality. The purpose of the researcher is to find out the relationship between anxiety level and sleep quality of Makassar College of Health Sciences students. The type of research used is observational analysis with a cross sectional approach method. The sample in this study was 275 people which were determined using the purposive sampling technique. The results of a statistical test of 275 people using the Kruskal-Wallis test showed that there was a relationship between anxiety level and student sleep quality with a value of p = 0.031 (P < ɑ = 0.05). The conclusion of this study is that there is a relationship between the level of anxiety and the quality of sleep of students at the Makassar College of Health Sciences. It is recommended for students who experience poor sleep quality to do self-therapy to reduce anxiety by means of deep breathing relaxation techniques, listening to music, murotul Al-Quran and avoiding procrastination from work or college assignments.